KONTRIBUSI MUTU PENDIDIKAN WILLIAM. EDWARD DEMING DALAM MENGEMBANGKAN KONSEP TOTAL QUALITY MANAGEMENT - Sirojudin, Didin; Al Ghozali, M. Dzikrul Hakim (EDUSCOPE: Jurnal Pendidikan, Pembelajaran, dan Teknologi, 2022)
Quality assurance or the quality of goods or products and services is an aspect that has always been a benchmark in the industrial world, especially where the level of success of a company can be measured from the products it produces (quality). This measure becomes very important in ensuring customer or consumer satisfaction to always be consistent in using the products or services of a company or educational institution, because educational institutions also offer services. Deming in Nasution explains that quality is conformity to market or consumer needs. Research on the Contribution of Educational Quality William. Edward Deming In developing the concept of Total Quality Management, the writer uses the method of literature or literature review, the aim is to see that the whole as a whole is more important than one part. Because it is hoped that descriptive data can be obtained. The result of this research is the Deming Prize or Deming Prize, to obtain this award the company/institution must register with the Deming Prize committee which then the company will be assessed with several assessment criteria as follows: A) policies and goals; B) its organization and operations; C) education and dissemination; D) collection and dissemination of information and its utilization; E) analysis; F) standardization; G) control; H) quality assurance rights I) influence and J) characterize future plans